2014
DOI: 10.1007/s00253-014-5749-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial management of arthropod pests of tea: current state and prospects

Abstract: Sustainable tea cultivation will rely increasingly on alternatives to conventional chemical insecticides for pest management that are environment-friendly and reduce the amount of pesticide residues in made tea. Entomopathogens can provide effective control, conserve biodiversity, and serve as alternatives to chemical insecticides under several conditions. Due to their specificity for insects, these pathogens including viruses, bacteria, and fungi are ideal candidates for incorporation in the integrated pest m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Many nutritional ingredients are produced in tea shoots, which are used as raw materials for commercial tea processing (Comblain et al, 2016). However, various tea plant pests jeopardize the quantity and quality of tea, such as the tea leaf beetle, one of the most serious pests affecting tea plants in China, Vietnam, Indonesia, Japan, and other teaproducing countries in Asia (Sun et al, 2010;Yang et al, 2013;Roy and Muraleedharan, 2014). Here, we reported a leaf beetle, Myllocerinus aurolineatus Voss in tea plant in Guizhou province, China.…”
Section: Introductionmentioning
confidence: 81%
“…Many nutritional ingredients are produced in tea shoots, which are used as raw materials for commercial tea processing (Comblain et al, 2016). However, various tea plant pests jeopardize the quantity and quality of tea, such as the tea leaf beetle, one of the most serious pests affecting tea plants in China, Vietnam, Indonesia, Japan, and other teaproducing countries in Asia (Sun et al, 2010;Yang et al, 2013;Roy and Muraleedharan, 2014). Here, we reported a leaf beetle, Myllocerinus aurolineatus Voss in tea plant in Guizhou province, China.…”
Section: Introductionmentioning
confidence: 81%
“…depends on the geographic region although several species are observed in more than one region (Roy et al, 2016). It is estimated that more than 1031 species of arthropods and 82 species of nematodes infest tea all over the world (Hazarika et al, 2009) and 380 species of phytophagous pests are reported from India alone (Roy & Muraleedharan, 2014). Some major tea pests are sucking pests, like tea mosquito bug ( Helopeltis theivora ), tea thrips ( Scirtothrips dorsalis ), chewing pests like looper caterpillar ( Buzura suppressaria ), red slug caterpillar ( Eterusia magnifica ) and mite pest, such as scarlet mite ( Brevipalpus phoenicis ), red spider mite ( Oligonychus coffeae ).…”
Section: Fungal Diseases and Pest Infestation In Teamentioning
confidence: 99%
“…The bacterial species within the genus Bacillus has broad significance; they produce industrially beneficial enzymes (Liszka et al, 2012), bacteriocins and antibiotics (Abriouel et al, 2011), insecticides (Bravo et al, 2013;Roy and Muraleedharan, 2014), and used as probiotics (Cutting, 2011). They are also responsible for food spoilage and human and animal diseases (Logan, 2012).…”
Section: Introductionmentioning
confidence: 99%